Penerapan Penerapan Model Discovery Learning pada Materi Garis dan Sudut untuk Meningkatkan Hasil Belajar Siswa - Janah, Miftahul; Baidowi, Baidowi; Suntoko, M. Iwan (Mandalika Mathematics and Educations Journal, 2025)
This research is a Classroom Action Research (CAR) aimed at improving students’ mathematics learning outcomes on the topic of Lines and Angles through the implementation of the Discovery Learning model. The problem in this study is the low initial understanding of geometry concepts among students, particularly in the topic of lines and angles, which negatively affects their mathematics learning outcomes. This is evident from the pretest results, which showed that only 4 students (9.3%) achieved the Minimum Mastery Criteria (MMC). The research was conducted in two cycles using the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research subjects consisted of 43 seventh-grade students from class VII E at SMPN 1 Mataram, who received treatment in the form of the Discovery Learning model implementation by the researcher. Data were collected through student activity observation sheets and learning outcome tests, which were then analyzed using descriptive quantitative and qualitative methods. In Cycle I, the learning focused on the types of angles (2 meetings), while in Cycle II, the focus was on the relationships between angles (3 meetings). The success criteria were determined based on students achieving MMC ≥ 75 and classical completeness ≥ 85%. The results showed an increase in classical completeness from 46.5% in Cycle I to 86% in Cycle II. Thus, the implementation of the Discovery Learning model proved effective in improving students' mathematics learning outcomes.